NEW NORMAL PADA INDUSTRI PERBANKAN DI TENGAH PANDEMIK COVID-19 - Kurniawan, I Gede Hartadi; Judge, Zulfikar; Olivia, Fitria (Jurnal Pengabdian Masyarakat AbdiMas, 2020)
Large-scale Social Restrictions (PSBB) that have been imposed in several regions of Indonesia have passed several times of extension from one period to the next. In the DKI Jakarta area, on June 5, 2020 passed the third period and entered the fourth period PSBB or also called the transition PSBB period or if it was likened to another term, the "New Normal" period. The period of a region can be said to have entered the term "New Normal" if the level of spread of the Covid-19 pandemic has entered a declining trend. The number of open unemployment is 3.5 million to 8.5 million people throughout 2020. "This means that the unemployment rate has the potential to rise from the current 5.2 percent to 5.3 percent to between 7.7 percent on a moderate scale and 10, 3 percent on a weight scale The significantly increased unemployment rate is highly correlated with the closure of various types of factories and businesses in line with the various rules in the PSBB regulations.Pandemic Covid-19 inevitably changes the habits that have been carried out by the hotel industry for example that is, we will not see breakfast facilities with buffets and various other facilities that may be a distance when using a swimming pool or fitness center.In the absence of breakfast services, there will automatically be potential for reducing the need for food raw material providers or decide to cooperate with a catering company as a provider of facilities n morning. It is also not possible for the banking industry to wait too long for debtor installments to return to their normal payment situation. In addition, the massive termination of employment is avoided as far as possible with the aim of reviving Micro, Small and Medium Enterprises (MSMEs) with a "New Normal" situation or a new normalcy adjusted to the health protocol Covid-19.Ã‚Â Keywords : Large-scale Social Restrictions (PSBB), Covid-19, bank